(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Cash inflow and outflow of cashew industries in study area Suggestions have been presented in form of strategy for development of cashew production in India as a source of income of Karnataka’s peasantry, described in the following manner. India ranks foremost in the world in the production of raw cashew nuts as well as in the export of cashew kernels, with the requirements of the processing sector, India’s dependence on imported nuts particularly from the East African countries to feed its processing sector continued for log. With decline in the production and collection of raw cashew nuts coupled with creation of processing capacities in the East African countries India’s imports of raw nuts reached critical level and the processing industry came under severe pressure for want of the main raw material. At the same time, Indian Kernels faced increasing competition in major consuming markets such as USA from supplies from countries such as Brazil, China and Mozambique, as also from other edible nuts. The situation called for a pragmatic approach to solve the raw nut shortage problem and to launch a new plan of action for increasing cashew production and productivity in the country. Concentrated efforts towards stepping up raw nut production commenced in the country only during the Fourth Five year plan period (1970-75) and were continued during the Fifth and Sixth plans. These were supplemented by the multi-State Cashew project implemented with financial assistance from the World Bank, in four cashew producing states with effect from September 1, 1980.